Squamous Cell Carcinoma of the External Auditory Canal: A Case Report - Harry Boamah; Glenn Knight; Joseph Taylor; Kevin Palka; Billy Ballard (Case Reports in Otolaryngology)
Squamous cell carcinoma of the temporal bone and external auditory canal is a rare tumor with a reported incidence of between 1 to 6 cases per million population per year. Because squamous cell carcinoma of the temporal bone and auditory canal is so rare, developing an adequate tumor staging system and treatment has been difficult. We present a case of squamous cell carcinoma of the external auditory canal in 65-year-old Hispanic female who presented with a 6-month history of right ear pain, 3-month history of serosanguineous right ear drainage, and symptoms of facial paralysis. Due to the extensive spread of her tumor into the middle ear at the time of diagnosis, her tumor was deemed unresectable and she received palliative chemotherapy and radiation therapy and was sent to Alice Hospice and died several weeks later.